The Role of Momentary Dissociation in the Sensory Cortex: A Neurophysiological Review and its Implications for Maladaptive Daydreaming - Roy, Anney; Girija, Varsha Subramanian; Kitzlerová, Eva (Medical Science Monitor, 2024)
Daydreaming, a form of spontaneous and self-generated mental process, may lead to the disintegration of attention from the immediate external environment. In extreme cases, patients may develop maladaptive daydreaming comorbid with dissociation. The examination of dissociative alterations frequently occurs within the framework of complex cognitive processes. While dissociation may be a neurological and psychological dysfunction of integration, transient dissociative occurrences, i.e., momentary dissociation may signify a dynamic interplay between attentional division and orientation within the sensory cortex. Furthermore, previous studies have recorded the interactivity of attention by stimuli onset with P3 event-related potentials and the active suppression of distractor positivity. In this context, during auditory and visual mismatch negativity, the sensory cortex may interact with attentional orientation. Additionally, distractor positivity during task-relevant stimuli may play a crucial role in predicting momentary dissociation since sensory cortices share cerebral correlates with attentional fluctuations during mental imagery. Thus, this theoretical review investigated the cerebral activities associated with attentional orientation and may be extended to mindfulness. By integrating these findings, we aim to provide a comprehensive understanding of dissociative states which may lead to a resolution for dissociative psychopathology.
Keywords: Dissociative Disorders; Electroencephalography; Humans; disociační poruchy; lidé; Evoked Potentials; elektroencefalografie; evokované potenciály; Attention; pozornost